2015
DOI: 10.1088/2051-672x/3/1/014002
|View full text |Cite
|
Sign up to set email alerts
|

Understanding error generation in fused deposition modeling

Abstract: Additive manufacturing offers completely new possibilities for the manufacturing of parts. The advantages of flexibility and convenience of additive manufacturing have had a significant impact on many industries, and optimizing part quality is crucial for expanding its utilization. This research aims to determine the sources of imprecision in fused deposition modeling (FDM). Process errors in terms of surface quality, accuracy and precision are identified and quantified, and an error-budget approach is used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 17 publications
1
32
0
Order By: Relevance
“…Most of the issues and downsides reported by the students about machine failures or FDM process accuracy are well documented in the literature (Armillotta, 2006, Bakar et al, 2010, Bochmann et al, 2015, Boschetto and Bottini, 2014, Dimitrov et al, 2006, Johnson et al, 2014, Mahesh et al, 2004, Pei et al, 2011. As concerns the fourth question about Changes, in order to solve the abovementioned problems related to the wrong clearances, students would modify the product geometry in terms of tolerances assigned to joints and integrated movable parts.…”
Section: "Difficulties In Designing a Component To Be Manufactured Bymentioning
confidence: 99%
“…Most of the issues and downsides reported by the students about machine failures or FDM process accuracy are well documented in the literature (Armillotta, 2006, Bakar et al, 2010, Bochmann et al, 2015, Boschetto and Bottini, 2014, Dimitrov et al, 2006, Johnson et al, 2014, Mahesh et al, 2004, Pei et al, 2011. As concerns the fourth question about Changes, in order to solve the abovementioned problems related to the wrong clearances, students would modify the product geometry in terms of tolerances assigned to joints and integrated movable parts.…”
Section: "Difficulties In Designing a Component To Be Manufactured Bymentioning
confidence: 99%
“…While all are important considerations, the most essential from the perspective of engineering design are the dimensional accuracy and repeatability of the final parts. It was observed that most of the problems with the dimensional accuracy in AM are due to the material behavior [16,[24][25][26] and to the limitations and mechanics of the processing equipment [27][28][29]. Since most AM processes involve heating the material past the melting temperature, shrinkage of the material is a concern as it cools in layers; this shrinkage can both destroy the dimensional integrity of the part and introduce residual stresses, potentially reducing the material fatigue life as well.…”
Section: Introductionmentioning
confidence: 99%
“…While all of these are important to examine, the most important from the perspective of engineering design are the dimensional accuracy and repeatability of the final parts. It has been observed that most of the problems with the dimensional accuracy in AM are due to the material behavior [13,[21][22][23] and to the limitations and mechanics of the processing equipment [24][25][26]. Since most AM processes involve heating the material past the glass transition temperature, shrinkage of the material is a concern; this shrinkage can both destroy the dimensional integrity of the part and introduce residual stresses, potentially reducing the material fatigue life as well.…”
Section: Of 27mentioning
confidence: 99%